1997
DOI: 10.1523/jneurosci.17-06-02018.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fate Specification and Symmetrical/Asymmetrical Divisions in the Developing Cerebral Cortex

Abstract: Two different modes of cell division are adopted by progenitor cells to generate the neurons and glia of the cerebral cortex: they either divide symmetrically to generate other progenitors or a pair of postmitotic cells or divide asymmetrically to generate both a progenitor and a postmitotic cell. In this study we used a lineage marker, the BAG retrovirus, in embryonic day 16 rats in combination with bromodeoxyuridine (BrdU) to identify patterns of cell generation in the cerebral cortex, and investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 62 publications
8
75
0
2
Order By: Relevance
“…The more recent use of a retroviral marker in combination with bromodeoxyuridine (BrdU) has shown that only pyramidal neurons maintain a close spatial relationship with their clonal relatives in the developing cortex, which can be achieved through radial migration (25). In contrast, labeled nonpyramidal cells were found, in agreement with earlier lineage analyses, as isolated cells or pairs of clonally neurons.…”
Section: Development Of Neuronal Lineagessupporting
confidence: 73%
“…The more recent use of a retroviral marker in combination with bromodeoxyuridine (BrdU) has shown that only pyramidal neurons maintain a close spatial relationship with their clonal relatives in the developing cortex, which can be achieved through radial migration (25). In contrast, labeled nonpyramidal cells were found, in agreement with earlier lineage analyses, as isolated cells or pairs of clonally neurons.…”
Section: Development Of Neuronal Lineagessupporting
confidence: 73%
“…In contrast, consistent with retroviral lineage tracing studies in vivo (5,(15)(16)(17)(18), analysis of the division patterns of isolated NE cells and their progeny has documented the coexistence, in vitro, of asymmetric and symmetric neurongenerating divisions of progenitors at the onset of neurogenesis (19)(20)(21). One possible explanation for this apparent discrepancy is the existence of neuronal progenitors other than the canonical NE cell dividing at the apical surface of the neuroepithelium.…”
mentioning
confidence: 76%
“…Retroviral lineage studies (5,15,16,18) and clonal analysis of isolated neuronal progenitors (19)(20)(21) have shown that neurons can be generated from both symmetric and asymmetric divisions. However, only asymmetric divisions have previously been reported from time-lapse analyses of neurongenerating divisions of NE͞radial glial cells occurring at the apical side of the VZ (7-9).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, early-born, deep-layer neurons are thought to be primarily derived from asymmetric neurogenic divisions of radial glial cells in the VZ, which are multipotent progenitors throughout the CNS (Heins et al, 2002;Malatesta et al, 2003). In contrast, later-born, upperlayer neurons are thought to be derived from the SVZ, a model that is currently supported by lineage tracing (Goldman, 1995), gene expression analyses (Ishii et al, 2000;Tarabykin et al, 2001) and the preferential occurrence of symmetrical neurogenic cell divisions in the SVZ (Haubensak et al, 2004;Kornack and Rakic, 1995;Mione et al, 1997;Miyata et al, 2004;Noctor et al, 2002Noctor et al, , 2004. Notably, in utero electroporation selectively targets apical VZ progenitors, while previous BrdU birthdating experiments identified the time of neuronal birth in each layer by labeling both VZ and SVZ progenitors.…”
Section: The Position Of Cells Electroporated and Birthdated At E155mentioning
confidence: 99%